High-carbon steel: microstructure and abrasive wear resistance of heat affected zone after welding with fast cooling - Brykov, M.N.; Efremenko, V.G.; Osipov, M.Yu.; Kapustyan, A.E.; Akrytova, T.A.; Kalinin, Yu. A. (Problems of Tribology, 2021)
The goal of this work is to estimate the abrasive wear resistance of heat affected zone (HAZ) after welding high-carbon low-alloy steel 120Mn3Si2 with fast cooling. The following benchmark data were used: microstructures of HAZ of 120Mn3Si2 steel after welding with cooling in water; abrasive wear resistance of different microstructure constituents of 120Mn3Si2 steel in two-body abrasive wear conditions. It is shown that high abrasive wear resistance of material in HAZ is provided in the vicinity of fusion line. The reason is unstable retained austenite which appears in HAZ as a result of quenching at fast cooling right after welding. The wear resistance of material in HAZ is altered by microstructural changes from austenite to austenite+martensite and finally martensite. The martensitic zone is about 0.5 mm wide and it is followed by zone of tempering of initial structure of steel. Zone of tempering is 1.5-2.0 mm wide and is the only zone of low abrasive wear resistance in HAZ of 120Mn3Si2 steel welded with fast cooling. Welding of 120Mn3Si2 steel with fast cooling in water results in welding joints which have as high wear resistant as the base material or even higher. This enables manufacturing flat welded elements with high wear-resistance and large surface area